2018
DOI: 10.1177/1120700018813208
|View full text |Cite
|
Sign up to set email alerts
|

Double-trabecular metal cup technique for the management of Paprosky type III defects without pelvic discontinuity

Abstract: Introduction: Modular reconstruction systems based on trabecular metal (TM) prosthetic components have been increasingly used in the last decade for the management of severe acetabular bone defects. The aim of this study was to assess the clinical and radiographic outcomes of double-cup technique for the management of Paprosky type III defects without pelvic discontinuity. Methods: A retrospective review was performed for all patients undergoing acetabular reconstruction with 2 TM cups at a tertiary referral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 23 publications
3
20
2
Order By: Relevance
“…Clinically, we found a significant and enduring improvement of the mHHS in our cohort at minimum 55months follow-up. Though the average score of 74.2 points at the latest follow-up is higher than previously described [3,10], it is lower than the mean score of 81 points of revision hip arthroplasty described by Löchel J et al [4]. After comparison the number of previous affected hip surgeries, we demonstrated that previous surgery is an important factor for mHHS score and Trendelenburg sign results.…”
Section: Clinical and Radiological Resultscontrasting
confidence: 73%
See 4 more Smart Citations
“…Clinically, we found a significant and enduring improvement of the mHHS in our cohort at minimum 55months follow-up. Though the average score of 74.2 points at the latest follow-up is higher than previously described [3,10], it is lower than the mean score of 81 points of revision hip arthroplasty described by Löchel J et al [4]. After comparison the number of previous affected hip surgeries, we demonstrated that previous surgery is an important factor for mHHS score and Trendelenburg sign results.…”
Section: Clinical and Radiological Resultscontrasting
confidence: 73%
“…In present study, we found no patients underwent re-revision surgery for any reasons over the followup period ( Table 3). There is no significant difference about cup survival in comparison with literatures at the latest follow-up [3,10]. Clinically, we found a significant and enduring improvement of the mHHS in our cohort at minimum 55months follow-up.…”
Section: Clinical and Radiological Resultscontrasting
confidence: 43%
See 3 more Smart Citations